Product Brand and Customer Loyalty: A Survey of the Nigeria Banking Industry - Marshal, Iwedi (Journal of Accounting, Business and Finance Research, 2017)
The banking industry have experience tremendous changes ranging from structural changes to technological advances which have turned the industry into self service industry where customer’s problems can be solved at any moment despite their location. Since the banking industry is intensely competitive, complex and dynamics due to the fact that all the banks offers same products and services that can easily be copied, as such the only way to differentiate oneself in this complex and dynamic banking environment is to offer same product and service brand with high quality at a cheaper price. However, the study examines how product brands influences customer loyalty in the banking industry in Nigeria. The study adopted the descriptive survey to study twenty two (22) commercial banks in Nigeria. Quarterly data ranging from 2009 through 2014 was collected from the CBN statistical bulletin and the analysis was conducted using mean, median, graphs and pie chart. The results obtained showed that product/service brand with high quality plays a critical role in influencing customers’ satisfaction and customers’ involvement which leads to customer loyalty.